Should drugs be decriminalised? Yes. Issue 7627 (8th November 2007) - Chand, Kailash
Abstract : Recent government figures suggest that the UK drug treatment programmes have had limited success in rehabilitating drug users, leading to calls for decriminalisation from some parties. Kailash Chand believes that this is the best way to reduce the harm drugs cause, but Joseph Califano thinks not